Indian languages in Singapore - Jain, Ritu (Edinburgh University Press, 2024)
Discussing the representation of the linguistic identity of Singapore‘s Indian community in social policies, this chapter explores the implications to maintenance and shift of the unrepresented languages. While only the majority language Tamil has been given official status in the language policy, other community languages have not been discouraged either. In fact, languages such as Bengali, Gujarati, Hindi, Punjabi, and Urdu have been accepted as optional subjects in education for students of Indian heritage. Yet others (e.g., Malayalam), with no support from governmental or institutional policies, are taught in after-hours community schools. Given the variance of support, this chapter uses an adaptation of the feature-factor matrix offered by Moag (2003) to evaluate factors considered significant in the loss/retention of non-official languages. While the 31 demographic, political, socio-cultural, and sociolinguistic factors have been proposed to predict the likelihood of survival for assessed languages, here they serve as a framework to assess both community attitude and ethnolinguistic vitality among the Indian speech communities in Singapore. The chapter draws on data from interviews with 29 families of diverse Indian language backgrounds to assess if these factors are facilitative of language use and the extent to which this indicates the likelihood of intergenerational language transmission. The chapter concludes with a discussion of the impact of language status and institutional recognition on the uptake and use of the institutionally non-recognised languages.